Training Needs of Extension Personnel in Agricultural Enginering - Nirmal Kumar, Mukesh Kumar Singh, Anil Kumar Dohare, (Indian Journal of Extension Education, 2022)
This study was conducted to identify the training needs in the area of agricultural engineering of the extension personnel working in the department of agriculture, horticulture, agricultural engineering and KVKs of M.P and Chhattisgarh. Results shown that major training needs identified in the area of Farm Machinery and Power were “Production and processing equipment and technology of agricultural and horticultural crops for small farmers” “Women friendly tools and implements in agriculture and horticulture”. “Mechanization in Horticulture”. “Machinery, equipment & technology”,“Harvesting and threshing equipment for income generation by custom hiring” majority of the extension personnel expressed training need in the area of Agro- Processing and Value Addition. The training need index was highest (0.32) for the theme “Advances in value addition of fruits and vegetables” in all the training needs studied under Agro Processing and Value Addition. Other theme of under this area is on the basis of TNI were “Farm level processing and value addition technology for agricultural produce” (TNI-0.29), “Food security and income augmentation though agro processing”(TNI-0.28), and “Processing and Utilization of soybean”.